2023
DOI: 10.3390/electronics13010098
|View full text |Cite
|
Sign up to set email alerts
|

Ship Classification Based on AIS Data and Machine Learning Methods

I-Lun Huang,
Man-Chun Lee,
Chung-Yuan Nieh
et al.

Abstract: AIS ship-type code categorizes ships into broad classes, such as fishing, passenger, and cargo, yet struggles with finer distinctions among cargo ships, such as bulk carriers and containers. Different ship types significantly impact acceleration, steering performance, and stopping distance, thus making precise identification of unfamiliar ship types crucial for maritime monitoring. This study introduces an original classification study based on AIS data for cargo ships, presenting a classifier tailored for bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…They concluded that XGBoost performed the best in the ensemble learning method for identification [46]. In addition, in some related studies in the fields of fault diagnosis and classification, XGBoost has shown greater advantages than other models, and the study in this paper is consistent with the results in [47][48][49][50].…”
Section: Discussion On the Effectiveness Of Xgboostsupporting
confidence: 83%
“…They concluded that XGBoost performed the best in the ensemble learning method for identification [46]. In addition, in some related studies in the fields of fault diagnosis and classification, XGBoost has shown greater advantages than other models, and the study in this paper is consistent with the results in [47][48][49][50].…”
Section: Discussion On the Effectiveness Of Xgboostsupporting
confidence: 83%